Vertical integration and patterns of divergence in European industries: A long-term input-output analysis - Fabio Ascione; Maria Enrica Virgillito (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2023)
Against a theoretical background which recognizes the gains from trade liberalization, this paper asks whether, and if so to what extent, economic integration as directly measured through vertically integrated value-added has increased or reduced convergence among European industries and related countries. To answer this question, we draw upon new input-output tables and sectoral divergence measures for 14 European countries and 19 sectors since 1970. Our novel database provides consistent long-run measures of international input-output linkages and sectoral dispersion in labor productivity and wages. We use these measures to study the timing and mechanisms that govern the relationship between economic integration and sectoral gaps, taking a European perspective and focusing on the role of international production fragmentation via input-output linkages. According to our findings, higher vertical integration has fostered divergence rather than convergence within industries. Lock-in effects in laggard positions coupled with positive feedback loops and increasing returns for leading positions are potential mechanisms to explain why the fruits of rising vertical integration are shared unequally between poor-performing industries and frontier industries.
Keywords: F6; F14; F15; D63; O47; 330; Input-output analysis; divergence; economic integration; Europe; trade liberalization